THE INFLUENCE OF MOTIVATION, SELF-EFFICACY AND FAMILY ENVIRONMENT ON STUDENTS’ INTEREST FOR ENTREPRENEURSHIP: Survey on Students of Management Study Program, Faculty of Economics at Slamet Riyadi University Surakarta - Suprayitno, Suprayitno; Ariati, Viola Verli (jfpublisher, 2022)
This study aims to explain the impact of motivation, self-efficacy, and family environment on students' interest in entrepreneurship. The research was conducted using a survey method on 2018 students from the Management Study Program at the Faculty of Economics, Slamet Riyadi University. Data collection techniques included questionnaires and observations. The sampling method used was purposive sampling, with 80 respondents who had taken entrepreneurship courses and were active students from the class of 2018. Based on the t-test results, motivation and family environment significantly influenced students' interest in entrepreneurship, whereas self-efficacy did not have a significant effect. Meanwhile, the F-test results showed that motivation, self-efficacy, and family environment collectively influenced students' entrepreneurial interests. The coefficient of determination (R2) was found to be 0.420, indicating that 42% of students' entrepreneurial interest is influenced by motivation, self-efficacy, and family environment, while the remaining 58% is affected by other variables not examined in this study. Therefore, students need to enhance their motivation, self-efficacy, and family support for entrepreneurship as preparation for their careers after graduation.